Utilisation of eggshells for preventing crack in precast concrete components / Mohd Danial Dahron and Suryani Ahmad - Dahron, Mohd Danial; Ahmad, Suryani (2024)
The use of eggshells in preventing cracks in precast concrete components offers a new and eco-friendly solution to an age-old problem. Cracks in concrete can compromise the strength and durability of structures, leading to costly repairs and safety concerns. This project explores how eggshells can be used as a self-healing material in precast concrete to enhance its longevity and sustainability. Our goals are to understand the current challenges in crack prevention, develop a way to mix eggshells into concrete, and test this method in both the lab and real-world conditions. The research combines an extensive review of existing studies with hands-on experiments. We hope to show that eggshells can significantly improve the performance of precast concrete, making it a more durable and environmentally friendly building material.